Chemosensitizing effect of neferine on cisplatin-resistant colorectal cancer: Identification of potential candidate genes and pathways through whole transcriptome profiling - Bharath Somasundram; Prasath Manogaran; Madavan Vasudevan; Vijaya Padma Viswanadha (Elsevier, 2022)
Background: Cisplatin drug resistance is a serious impediment for the therapeutic success against platinum-based chemotherapy in several cancers. Neferine, a bisbenzylisoquinoline alkaloid from Nelumbo nucifera is an effective anticancer agent which has shown potential to reverse the chemo-resistance in cisplatin-resistant colorectal cancer (CRC) cells. Aim: The purpose of the study to explore the mechanism of chemo-sensitizing effect of neferine in cisplatin-resistant CRC cells through whole transcriptome analysis. Methods: Cisplatin-resistant CRC cell line HCT-15 was established in vitro condition. Whole transcriptome analysis was performed to screen cisplatin-resistant CRC cells versus sensitive CRC cells and neferine-treated versus untreated cisplatin-resistant CRC cells. Transcriptome raw data quality control, normalization, differently expressed genes (DEGs), gene regulatory pathway networking were performed using standard bioinformatics tools. Real-time PCR and Western blot analyses were performed to validate the transcriptome profiling DEGs data. Results: The MTT assay and propidium iodide (PI) uptake revealed that neferine inhibits the proliferation of cisplatin-resistant CRC cells. Differential expression of 2081 genes was observed in cisplatin-resistant CRC cells compared to sensitive CRC cells. Also, neferine treatment in cisplatin-resistant CRC cells revealed differential expression of 1262 transcripts compared to untreated cells. The genes involved in cell cycle, DNA repair, translesion synthesis (TLS), minichromosome maintenance (MCM) complex, multiple proteasome subunits and FA/BRCA pathway were differentially expressed in cisplatin-resistant CRC cells which were counteracted by neferine treatment. Conclusion: Results of the current study suggest altered expression of genes involved in DNA replication and repair, DNA damage and bypass, MCM complex and proteasome subunits and FA/BRCA pathway in cisplatin resistance. Further, neferine treatment corrected the aberrant expression of the genes in cisplatin-resistant CRC cells.